Pengaruh Kualitas Pengungkapan Sustainable Development Goals (SDGs) dan Tata Kelola Perusahaan terhadap Efektivitas Kinerja Perusahaan BUMN di Indonesia - Naufal Abyan Hanif; Mukhamad Zaenal Afandi; Wildan Hilman Nafian; Dien Noviany Rahmatika (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The effectiveness of Sustainable Development Goals (SDGs) disclosure and corporate governance implementation remains a critical issue for Indonesian state-owned enterprises (BUMN), particularly regarding their contribution to corporate performance. Existing studies show inconsistent findings, and a comprehensive synthesis of the literature is still limited. This study aims to systematically review empirical evidence on the influence of SDGs disclosure quality and corporate governance on the effectiveness of BUMN performance in Indonesia. Using a Systematic Literature Review (SLR) approach, this research analyzes 25 peer-reviewed articles published between 2014 and 2024, collected from national and international academic databases. The review process involved structured searching, screening, and synthesis of relevant studies, supported by bibliometric analysis using VOSviewer to identify research trends and gaps. The findings indicate that SDGs disclosures in BUMN are predominantly qualitative and descriptive, which limits their measurable impact on financial performance indicators such as ROA and ROE. Corporate governance functions as an internal monitoring mechanism; however, it has not consistently strengthened the relationship between SDGs disclosure and company performance. Firm size and market conditions appear to exert a more dominant influence. Overall, the study highlights the need for more quantitative and integrated SDGs reporting, as well as more effective governance practices, to enhance the long-term performance and accountability of BUMN.